Ontogeny of the anuran urostyle and the developmental context of evolutionary novelty - Senevirathne, Gayani (Proc Natl Acad Sci U S A, 2020)
Developmental novelties often underlie the evolutionary origins of key metazoan features. The anuran urostyle, which evolved nearly 200 MYA, is one such structure. It forms as the tail regresses during metamorphosis, when locomotion changes from an axial-driven mode in larvae to a limb-driven one in adult frogs. The urostyle comprises of a coccyx and a hypochord. The coccyx forms by fusion of caudal vertebrae and has evolved repeatedly across vertebrates. However, the contribution of an ossifying hypochord to the coccyx in anurans is unique among vertebrates and remains a developmental enigma. Here, we focus on the developmental changes that lead to the anuran urostyle, with an emphasis on understanding the ossifying hypochord. We find that the coccyx and hypochord have two different developmental histories: First, the development of the coccyx initiates before metamorphic climax whereas the ossifying hypochord undergoes rapid ossification and hypertrophy; second, thyroid hormone directly affects hypochord formation and appears to have a secondary effect on the coccygeal portion of the urostyle. The embryonic hypochord is known to play a significant role in the positioning of the dorsal aorta (DA), but the reason for hypochordal ossification remains obscure. Our results suggest that the ossifying hypochord plays a role in remodeling the DA in the newly forming adult body by partially occluding the DA in the tail. We propose that the ossifying hypochord-induced loss of the tail during metamorphosis has enabled the evolution of the unique anuran bauplan.